MW-mile charging methodology for wheeling transaction - Hassan, Mohammad Yusri (2004)
Deregulation of the electric utility industry has taken place in many countries. This resulted in the unbundling of the vertically integrated utilities into separate generation, transmission and distribution businesses. Since then, the pricing of the use of transmission system has become one of the major issues. The issue concerns the way the cost of transmission services is satisfactorily allocated among the involved parties. In the context of the transmission utilities, the issue is how the cost of transmission service can be recovered while in the customers of transmission services point of view, the issue is how such services can be offered at the most reasonable price. Several strategies for pricing the use of transmission services have been proposed but there is no clear evidence on which one is better in providing adequate economic signal to the different parties. This thesis introduces a new approach called Negative Flow Sharing Approach to allocate the wheeling transaction charges among the users in transmission services. The proposed approach was developed using the properties of MW-mile method but taking into consideration the economic benefits of both trading parties through analysing their shares in negative power flow or counter flow. This approach is incorporated with the Justified Distribution Factor and an Incremental Absolute Approach to form a better wheeling charge allocation scheme that can overcome the problem that arises due to the allocation method, identification of counterflow users and revenue reconciliation of transmission services. Four case studies which are based on the 5 bus system, 9 bus system, IEEE-14 bus system and the 6 bus system were used in order to evaluate its concept and application. This thesis concludes with discussions on the case studies results by highlighting the merit of the proposed approach over the existing MW-mile approaches in providing sufficient return revenue to the transmission owner as well as a fair charge to the transmission user regardless of transaction arrangements and locations.